Alcohol use and risk of vehicle accidents: cross-sectional study in the city of São Paulo, Brazil - Oliveira, Janaina Barbosa de; Kerr-Corrêa, Florence; Lopes, Ícaro Caresia; Vitti Junior, Walter; Nunes, Hélio Rubens de Carvalho; Lima, Maria Cristina Pereira (São Paulo Medical Journal, 2020)
BACKGROUND: Harm to other people caused by an individual under the influence of alcohol (UIA) can occur in a variety of relationship situations between the drinker and these other people. OBJECTIVES: To estimate the prevalence of the risk of vehicle accidents (RVA) involving people who are UIA, according to sociodemographic variables, respondent alcohol use and gender. DESIGN AND SETTING: Cross-sectional study, in which a household survey was carried out on a cluster-stratified representative sample of urban residents in the city of São Paulo. METHODS: The final sample was composed of 1,155 subjects aged 18-59 years, who were interviewed using the GENACIS Harm-to-Others questionnaire. Individuals were defined as having been harmed if an affirmative response was given to at least one of the questions that refers to RVA involving people who had been UIA in the last twelve months. Post-stratification weights were calculated to adjust for the study design and for no response. Since the outcome was binary, logistic regression was used in multivariable analysis. RESULTS: The final response rate was 58.6%. The overall prevalence of RVA was 13.6% (95% confidence interval, CI 11.0-16.7): 16.6% among men and 10.8% among women. After the logistic regression, age remained as a protective factor (odds ratio, OR 0.95) and binge drinking as a risk factor (OR 2.03). CONCLUSION: This study showed that binge drinking was associated with RVA